A Student's Guide Through the Great Physics Texts Volume III: Electricity, Magnetism and Light - Kuehn, Kerry; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book provides a chronological introduction to the electromagnetic theory of light, using selected extracts from classic texts such as Gilbert$1 (Bs De Magnete, Franklin$1 (Bs Experiments and Observations on Electricity, and Huygens$1 (BTreatise on Light. Particular attention is given to the works of Faraday, Maxwell and Heaviside, scientists who unified the formerly separate disciplines of electricity, magnetism and light. Their electromagnetic theory$1 (Bdeveloped during the 19th century$1 (Bwould lead to the invention of modern radar, electrical power grids, and telecommunication networks. Each chapter of this book begins with a short introduction followed by a reading selection. Carefully crafted study questions draw out key points in the text and focus the reader$1 (Bs attention on the author$1 (Bs methods, analysis and conclusions. Numerical and laboratory exercises at the end of each chapter test the reader$1 (Bs ability to understand and apply key concepts from the text. Electricity, Magnetism and Light is the third of four volumes in A Student$1 (Bs Guide through the Great Physics Texts. This book grew out of a four-semester undergraduate physics curriculum designed to encourage a critical and circumspect approach to natural science while at the same time preparing students for advanced coursework in physics. This book is particularly suitable as a college-level textbook for students of the natural sciences, history or philosophy. It can also serve as a textbook for advanced high-school or home-schooled students, or as a thematically-organized source-book for scholars and motivated lay-readers. In studying the classic scientific texts included herein, the reader will be drawn toward a lifetime of contemplation. .s
From the Contents: Iron, Loadstones and Terrestrial Magnetism -- The Life and Death of a Magnet -- Conservation of Electrical Charge -- Muschenbroek's Wonderful Bottle -- Thunder and Lightning -- Coulomb's Law -- The Dawn of Electro-Magnetism -- Electric Currents, Magnetic Forces -- Work and Weight -- Kinetic and Potential Energy -- Conservation of Energy.
Keywords: Physics; Philosophy and science; Atoms; Optics; Optoelectronics; Plasmons (Physics).; Physics; History and Philosophical Foundations of Physics; Philosophy of Science; Optics, Optoelectronics, Plasmonics and Optical Devices; Atomic, Molecular, Optical and Plasma Physics; Electronic books